A comparative study of pleural effusion in water area, water temperature and postmortem interval in forensic autopsy cases of drowning - Akiko Ishigami (Nature Portfolio, 2021)
Abstract Japan is surrounded by the sea and is also a mountainous country with many rivers. Japan has the second- highest rate of deaths caused by drowning in the world. Pleural effusion (PE) is one of the major findings at autopsy. It is found in approximately 80% of drowning mortalities and is observable for a relatively long postmortem interval (PMI). We focused on the amount of pleural fluid in drowning cases, discussed the relationship of PE with the drowning environment, water temperature, and postmortem interval, and established more simple and practical criteria for the diagnosis of drowning. We measured the weight of the lungs, PE, and their sum as the intrathoracic (IT) weight (total weight of lungs + pleural effusion), and calculated the PE ratio [(PE weight/IT weight) × 100]. A total of 130 drowning deaths diagnosed through forensic autopsies were investigated in this study. The cases were classified by drowning environment (freshwater, brackish water, and seawater), water temperature (under 20 °C, more than 20 °C), and postmortem interval (less than 1 day, 1–3 days, more than 3 days). The present study demonstrated that the PE ratio may be more effective for the diagnosis of drowning. Moreover, the accumulation of PE is affected by drowning environment, water temperature, and PMI. Collectively, it is important to assess the PE ratio and consider these factors in autopsy cases of victims found in water.